2020
DOI: 10.1177/0972150920974143
|View full text |Cite
|
Sign up to set email alerts
|

Adopting a Core Competency Approach to Model Succession-planning Management: A Case Study of Iranian National Gas Company

Abstract: This study aimed to present a succession-planning management model with a core competency approach in the Iranian National Gas Company. For this purpose, qualitative and quantitative (mixed) methods were employed. The research population of the qualitative phase included 11 experts of the Iranian National Gas Company and 5 university professors, all selected by the purposeful sampling method. The data collection instrument was a semi-structured interview, and content analysis was exploited for data analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While our review is believed to be the first that associated intrinsic and extrinsic factors with SP&M, our findings were consistent with other reviews. For instance, Bazneshini et al (2020) found several components that are related with SP&M, such as cultural factor, managerial factor, personal competency and managerial competency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our review is believed to be the first that associated intrinsic and extrinsic factors with SP&M, our findings were consistent with other reviews. For instance, Bazneshini et al (2020) found several components that are related with SP&M, such as cultural factor, managerial factor, personal competency and managerial competency.…”
Section: Discussionmentioning
confidence: 99%
“…(Santora et al, 2019;Carter et al, 2019;Ghee et al, 2015). Social identity (Glover, 2014;Tietjen-Smith Hersman, & Block, 2020;Roche, et al, 2021;Sheridan et al, (Bazneshini et al, 2020;Mehrtak et al, 2014;Phillips, 2020;Maciel et al, 2015) Organizational culture (Arham et al, 2021;Al Suwaidi et al, 2020;Ahmad et al, 2020) Training and development (Arham et al,…”
Section: Extrinsic Factors Associated With Succession Planning and Ma...mentioning
confidence: 99%
“…As cited by Bazneshini et al (2020) the core competency approach has a vital role in the entire process of the succession planning system. Al-Mannaee and Ryan (2018) conducted a study in a large oil factory of 375 participants using competency model as the theoretical framework.…”
Section: Theme Fivementioning
confidence: 99%
“…Thus, the performance appraisal discussion is enhanced through competency models. Bazneshini, Golafshani, Rahmanseresht and Rabiei (2020) explained that the critical competencies needed at any leadership level enable selecting and evaluating the present and future competent leaders. The competency model supports organizational change in developing systematic strategies to support the organization.…”
Section: Theme Eightmentioning
confidence: 99%